1990
DOI: 10.1080/02701367.1990.10607493
|View full text |Cite
|
Sign up to set email alerts
|

Television Viewing and Physical Fitness in Adults

Abstract: The purpose of this study was to determine the extent to which time spent watching television is associated with cardiovascular fitness among 8,885 adults. Potential confounding effects of age, gender, smoking, length of work week, time reported exercising each week, and obesity were also examined. Subjects who watched TV more than 4 hours per day (frequent viewers) were 0.37 times as likely to be physically fit as those who watched TV less than 1 hour per day (infrequent viewers) with age and gender controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 12 publications
0
28
0
2
Order By: Relevance
“…Por un lado, encontramos trabajos que afirman que el ocio tecnológico es uno de los factores que pueden influenciar la dedicación a la práctica de AF (Kimm et al, 1996;Shannon et al, 1991;Bernard et al, 1995;). Por otro lado, existen estudios que no encuentran ninguna relación (Tucker, 1990;Cantera, 1997;Biddle, 2003). Estas discrepancias pudieran ser debidas, al igual que hemos manifestado anteriormente, a los diferentes criterios utilizados a la hora de clasificar el grado de sedentarismo de la población adolescente.…”
Section: Discussionunclassified
“…Por un lado, encontramos trabajos que afirman que el ocio tecnológico es uno de los factores que pueden influenciar la dedicación a la práctica de AF (Kimm et al, 1996;Shannon et al, 1991;Bernard et al, 1995;). Por otro lado, existen estudios que no encuentran ninguna relación (Tucker, 1990;Cantera, 1997;Biddle, 2003). Estas discrepancias pudieran ser debidas, al igual que hemos manifestado anteriormente, a los diferentes criterios utilizados a la hora de clasificar el grado de sedentarismo de la población adolescente.…”
Section: Discussionunclassified
“…Although results of cross-sectional studies that have examined associations between television viewing and total physical activity energy expenditure have been inconsistent (14,36,68,81,82), several intervention studies targeting reductions in television viewing among children have shown promise. One study with third and fourth graders used a TV time manager (locking device) for home televisions and an 18-session school-based curriculum (67).…”
Section: Television Viewing Reduction Interventionsmentioning
confidence: 99%
“…Television has been cited as a contributing factor to higher dietary energy or fat intake (29,36). Exposure to food advertising, especially commercials for fast food or convenience foods, may influence viewers' food choices toward higher-fat or higher-energy foods (14,29,36,43,44,76,81,82). Television is the most widely used advertising medium, which is not surprising given that televisions are present in 98% of US households and adults spend an average of 2 h per day watching TV (60).…”
Section: Advertising Promotion and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, outros achados associam esse hábito ao menor nível de condicionamento físico 50 , dislipidemia 49 , pressão arterial elevada 51 , diabetes tipo II 52 e síndrome metabó-lica 19 . De forma complementar, nossos resultados evidenciam, de forma inédita, a associação entre o hábito de ver TV por períodos prolongados e o consumo alimentar não saudável em adultos no país.…”
Section: -2011unclassified